If you're reading this, it's too late - Bosch, Pseudonymous; Ford, Gilbert (New York : Little, Brown and Company, 2009)
Cass and Max-Ernest discover the Museum of Magic, unscramble more coded messages, and solve new mysteries in their attempt to thwart the Terces Society's ambitions of discovering immortality.
Keywords: Immortality -- Juvenile fiction; Action and adventure fiction